Implementing the United Nations Sustainable Development Goals for the Systems Engineering of Multinational Corporations. Issue 1 (16th August 2018) - Brooks, Ian; Longhurst, James; Kossmann, Mario; Odeh, Mohammed
Abstract: The United Nations Sustainable Development Goals (SDGs) were adopted in 2015 by 193 countries. They can be characterised as sustainability 'requirements' for the global system. This paper provides a vision of how Multinational Companies (MNCs) are likely to experience the SDGs and their implications for Systems Engineering (SE) of the Enterprise. The SDGs do not have the status of international law and may be implemented differently in different countries over the period to 2030. MNCs will face choices about how they wish to comply today in anticipation of future requirements. Thereby, they also have the opportunity to avoid systems sustainability failures later on. This paper presents an initial approach to implementing the SDGs in the form of business requirements. The research will pave the ground for the development of a systematic framework for the adoption, monitoring and assessment of the SDGs in an SE context.